Analisis Kecemasan Karir pada Siswa dan Mahasiswa - Hazla, Nadratul; Meilani, Wulan; Aprisya, Safa; Tsaqila Shainy, Mutiara; Azzahrah, Naeza; Raisya Wandiana, Marhama (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
Career anxiety is described as a condition or situation where an individual is unable to make a decision in choosing a career because of an interception situation in the decision-making process. Each individual has different levels of anxiety. The purpose of this study is to understand, measure, and manage the impact of anxiety experienced by individuals related to aspects of their careers. This study was conducted using a quantitative descriptive method, involving approximately 108 participants consisting of high school students and college students. This study is expected to provide an in-depth understanding of the factors that influence career anxiety, so that more effective strategies and programs can be developed to help them overcome this anxiety.